From the Pulpit to the Feed: The Transformation of Da'wah Rhetoric and Its Relevance to the Formation of Millennial Islamic Identity - Muhammad Deni Azhari (Institut Agama Islam Sunan Giri Ponorogo, 2026)
The proliferation of social media platforms such as Instagram, YouTube, and TikTok has fundamentally altered the way Islamic preaching (da'wah) is composed, delivered, and consumed in Indonesia. What was once bound to the linear, face-to-face structure of the khutbah (sermon) delivered from the pulpit has been reconfigured into short, algorithmically circulated, and highly visual